Design Development and Evaluation of Water Dispersible Tablet of Aceclofenac Using Synthetic Superdisintigrants - Kumar, Anil; Agrawal, Dilip; Khinchi, Mahaveer Prasad; Soni, Shankar Lal; Singh, Surya Pratap (Asian Journal of Pharmaceutical Research and Development, 2015)
Aceclofenac has been shown to have potent analgesic and anti-inflammatory activities, similar to indomethacin and diclofenac and due to its preferential cox-2 blockade it has better safety than conventional NSAIDs with respect to adverse effects on gastrointestinal and cardiovascular system. Aceclofenac is superior form other NSAIDs as it has selectivity for cox-2, a beneficial cox inhibitor, well tolerated, better GI tolerability and improved cardiovascular safety when compared to other selective cox-2 inhibitors. Aceclofenac has a faster and more potent effect than the other NSAIDs. Aceclofenac has an outstanding anti-inflammatory profile, involving a classical inhibition of prostaglandins E2 , a decrease in the expression of several cytokines including interleukin and tumor necrosis factor. It also inhibits activated oxygen species production and influences cell adhesion. Thus it can be concluded that Aceclofenac may be a better option for the management of pain.